1989
DOI: 10.1016/0092-8674(89)90752-6
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of a serine protease, myeloblastin, causes growth arrest and differentiation of promyelocytic leukemia cells

Abstract: Cells from the human leukemia cell line HL-60 undergo terminal differentiation when exposed to inducing agents. Differentiation of these cells is always accompanied by withdrawal from the cell cycle. Here we describe the isolation of a cDNA encoding a novel serine protease that is present in HL-60 cells and is down-regulated during induced differentiation of these cells. We have named this protease myeloblastin. Down-regulation of myeloblastin mRNA occurs with both monocytic and granulocytic inducers. Myelobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
178
0
3

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(182 citation statements)
references
References 55 publications
1
178
0
3
Order By: Relevance
“…PR3 is a major target Ag of antineutrophil cytoplasmic Abs (15, 16) and degrades extracellular matrix proteins (13). PR3 is also shown to activate many types of cells (12,(17)(18)(19)(20), although the underlying mechanism was unclear. Therefore, the present study may provide one of the mechanisms of the cell activation by PR3 through PAR-2, and suggests that PR3 could activate the PAR-2-expressing cells, and regulate a number of inflammatory processes, and that the control of PAR-2-activating proteinases including PR3 at inflammatory sites might be beneficial in the regulation of inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PR3 is a major target Ag of antineutrophil cytoplasmic Abs (15, 16) and degrades extracellular matrix proteins (13). PR3 is also shown to activate many types of cells (12,(17)(18)(19)(20), although the underlying mechanism was unclear. Therefore, the present study may provide one of the mechanisms of the cell activation by PR3 through PAR-2, and suggests that PR3 could activate the PAR-2-expressing cells, and regulate a number of inflammatory processes, and that the control of PAR-2-activating proteinases including PR3 at inflammatory sites might be beneficial in the regulation of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…PR3 is a major target Ag of anti-neutrophil cytoplasmic Abs in Wegener's granulomatosis, a debilitating autoimmune disease characterized by necrotizing vasculitis (15,16). It has recently been shown that PR3 exhibits many biological functions, including the degradation of extracellular matrix proteins (13), regulation of myeloid differentiation (12,17), enhancement of TNF-␣ and IL-1␤ release from human monocytic cell lines (18), production of IL-8 and monocyte chemoattractant protein-1 (MCP-1) by human endothelial cells (19,20), and antibacterial action (21), all of which indicate that cell-bound and secreted soluble PR3 actively contribute to inflammatory processes, although the underlying mechanism is unclear to date.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since activated neutrophils express PR3 on their surface [5], it could facilitate their migration through basement membranes. PR3 may be instrumental in host defense and regulation of proliferation and differentation of hematopoetic cells [2,6]. PR3 can also proteolytically process interleukin 8 into a chemotactically more potent form [7], and cleave the mammalian heat shock protein hsp28 [8].…”
Section: Introductionmentioning
confidence: 99%
“…Amino acid residues at positions 103, 119, and 120 are polymorphic in human populations, accounting for three different protein sequences (V103 or I103 in combination with A119 and T120, and I103 in combination with T119, S120). Evolutionary comparisons, however, suggest that V103, A119, and T120 (20)(21)(22) of hPR3 represent the ancestral allele (Fig. 2).…”
Section: Strategy For Mapping Conformational Epitopesmentioning
confidence: 99%